2022
DOI: 10.1021/acs.est.2c00758
|View full text |Cite
|
Sign up to set email alerts
|

NOx Reduction over Smart Catalysts with Self-Created Targeted Antipoisoning Sites

Abstract: Selective catalytic reduction of NO x in the presence of alkali (earth) metals and heavy metals is still a challenge due to the easy deactivation of catalysts. Herein, NO x reduction over smart catalysts with self-created targeted antipoisoning sites is originally demonstrated. The smart catalyst consisted of TiO2 pillared montmorillonite with abundant cation exchange sites to anchor poisoning substances and active components to catalyze NO x into N2. It was not deactivated during the NO x reduction proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The results showed that NO + O 2 was adsorbed on the surface of the catalyst with different forms of nitrates, and the monodentate nitrate and bridged nitrate reached adsorption saturation. As shown in Figure b, it was obvious that the monodentate nitrate species (1433 cm –1 ) disappeared at 150 °C, whereas the bidentate nitrate (1310 cm –1 ) band increased with elevated temperature . The adsorption peak at 1310 cm –1 was slightly weaker and shifted to a higher wave number.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The results showed that NO + O 2 was adsorbed on the surface of the catalyst with different forms of nitrates, and the monodentate nitrate and bridged nitrate reached adsorption saturation. As shown in Figure b, it was obvious that the monodentate nitrate species (1433 cm –1 ) disappeared at 150 °C, whereas the bidentate nitrate (1310 cm –1 ) band increased with elevated temperature . The adsorption peak at 1310 cm –1 was slightly weaker and shifted to a higher wave number.…”
Section: Resultsmentioning
confidence: 90%
“…As shown in Figure 11a, only chelating nitrite (1270 cm −1 ) and monodentate nitrate (1433 cm −1 ) could be detected on the surface of the Ti-OMS-2-20%-PTFE catalyst in the first 9 min. 60 With the extension of adsorption time, the peak at 1270 cm −1 shifted to 1242 cm −1 . 61,62 It indicated that chelating nitrite was unstable and finally changed into bridged nitrate.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Selective catalytic reduction of NO x with ammonia (NH 3 -SCR) is considered an effective method to remove NO x . Herein, V 2 O 5 -WO 3 /TiO 2 catalysts have been commercially used for industrial and mobile sources. Currently, in addition to the toxicity of vanadium, SCR catalysts face considerable deactivation by alkali metals in the flue gas in practical applications, especially for alkali-rich stack gases such as power plants fueled by biomass. It has been observed that the physical poisoning of alkali metals on vanadia-based catalysts blocks the pore structures and harshly affects reactant diffusion. Conversely, chemical poisoning is caused by the reduction of Brønsted acidity. , …”
Section: Introductionmentioning
confidence: 99%